Asthma Exacerbation during the COVID-19 Pandemic - Nur Indah Sawitri; Betty Roosihermiatie; Arga Setyo Adji; Syalomitha Claudia Stefani Angel; Vira Aulia Kusuma Wardani; Riami Riami (Jurnal Respirasi, 2023)
Introduction: Asthmatics, especially uncontrolled asthmatics, must be vigilant during the COVID-19 pandemic to avoid major respiratory complications. This study aimed to describe these characteristics in emergency unit patients with asthma and COVID-19 at Haji General Hospital, Surabaya, an East Java referral hospital. Methods: The study gathered medical information on 160 asthma patients from March to December 2021. The collected data were related to socioeconomics, allergy history, family allergy history, and medications. Results: 160 confirmed cases of asthma occurred during COVID-19 at Haji General Hospital, Surabaya. Most adult asthma sufferers were women (59.2%), high school graduates (31.25%), housewives (21.2%), had payment method with Social Health Insurance Administration Body (BPJS) insurance (73.8 %), had a history of drug allergies (11.5%), had no family history of allergies (50.8%), and used albuterol control drugs (10.7%). Meanwhile, the majority of children with asthma were boys (53.3%), did not attend school or did not finish elementary school (33.3%), did not work (33.3%), had payment method with BPJS (73.3%), had a history of allergies to seafood and cow's milk respectively (10%), had no family history of allergies (40%), and used albuterol control drugs (16.7%). Conclusion: The proportion of asthma in the emergency unit was dominated by women over 18 years old with a high school education. Most patients were housewives and used BPJS. Many of them had a history of allergies to medications (not asthma medication), and there was no family history of allergies. Commonly used medications were albuterol to control asthma.